2012
DOI: 10.1890/11-0750.1
|View full text |Cite
|
Sign up to set email alerts
|

Population‐level compensation impedes biological control of an invasive forb and indirect release of a native grass

Abstract: The intentional introduction of specialist insect herbivores for biological control of exotic weeds provides ideal but understudied systems for evaluating important ecological concepts related to top-down control, plant compensatory responses, indirect effects, and the influence of environmental context on these processes. Centaurea stoebe (spotted knapweed) is a notorious rangeland weed that exhibited regional declines in the early 2000s, attributed to drought by some and to successful biocontrol by others. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 40 publications
4
48
0
Order By: Relevance
“…The data are inconsistent about the effects of precipitation on other survival and growth stages. Other results suggest that drought relief increased rosette mortality or has minimal effects on juvenile densities (Corn et al 2007, Ortega et al 2012, so no precipitation effects were included for growth or rosette survival. There is an interaction between precipitation and the effect of plant competition on spotted knapweed (Maron and Marler 2008); however, data do not indicate a correlation between precipitation and stem density or number of flowers (Ortega et al 2012; T. R. Seastedt, unpublished data).…”
Section: Model Descriptionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data are inconsistent about the effects of precipitation on other survival and growth stages. Other results suggest that drought relief increased rosette mortality or has minimal effects on juvenile densities (Corn et al 2007, Ortega et al 2012, so no precipitation effects were included for growth or rosette survival. There is an interaction between precipitation and the effect of plant competition on spotted knapweed (Maron and Marler 2008); however, data do not indicate a correlation between precipitation and stem density or number of flowers (Ortega et al 2012; T. R. Seastedt, unpublished data).…”
Section: Model Descriptionsmentioning
confidence: 99%
“…In the 10-30 years following the release of biological controls, spotted knapweed populations have declined while biological control populations have increased or persisted , 2008, Seastedt et al 2007, Gayton and Miller 2012. However, an experiment by Ortega et al (2012) demonstrated that spotted knapweed populations exhibited a compensatory response adult mortality: replacement of dead adults with increased numbers of rosettes becoming adults. The result was that there was no net change in adult density despite an increase in adult mortality due to biological controls (Ortega et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following invasion, knapweed forms peripherally enlarging monocultures that seed profusely, have allelopathic effects on susceptible species, and negatively impact ecosystem richness and diversity (Watson and Renney 1974, Schirman 1981, Tyser 1992, Sheley et al 1998, Kedzie-Webb et al 2001, Thorpe et al 2009). While it is known that knapweed can be controlled using a variety of methods including herbicide application (Rice • 283 et al 1997), biological controls (Story et al 2006, but see Ortega et al 2012), and controlled burning (MacDonald et al 2007), resurgence of knapweed is very likely without the formation of a competitive, native community (Sheley et al 1996), especially on sites in which seeds from previous infestations are present in the seed bank (Sheley et al 1996, Carpinelli et al 2004. As diverse native plant communities are more capable of resisting knapweed invasion (Kennedy et al 2002, Bakker and Wilson 2004, Maron and Marler 2007, it is important during any restoration project to ensure that such diverse native systems are reestablished.…”
mentioning
confidence: 99%